2018
DOI: 10.1186/s13071-018-2697-8
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of long non-coding RNA expression profiles uncovers a Toxoplasma-induced negative regulation of host immune signaling

Abstract: BackgroundToxoplasma gondii is an obligate intracellular protozoan parasite that can infect mammalian cells and thereby regulate host gene expression. The long non-coding RNAs (lncRNAs) have been demonstrated to be an important class of RNA molecules that regulate many biological processes, including host-pathogen interactions. However, the role of host lncRNAs in the response to T. gondii infection remains largely unknown.MethodsWe applied a microarray approach to determine the differential expression profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…It is also clear that infectious pathogens may influence the expression of host lncRNA [28]. Using a microarray-based profiling approach, Liu et al [37] and Menard et al [38] independently evaluated the global lncRNA transcriptome in cells infected with T. gondii tachyzoites. There are many methodological differences between our investigation and these two studies, including molecular biological methods, strains of parasite, and host species and host cell population, all of which may impact experimental results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also clear that infectious pathogens may influence the expression of host lncRNA [28]. Using a microarray-based profiling approach, Liu et al [37] and Menard et al [38] independently evaluated the global lncRNA transcriptome in cells infected with T. gondii tachyzoites. There are many methodological differences between our investigation and these two studies, including molecular biological methods, strains of parasite, and host species and host cell population, all of which may impact experimental results.…”
Section: Discussionmentioning
confidence: 99%
“…However, taking a discovery approach, both other groups found that the infection dysregulated substantial numbers of lncRNAs involved in the immune response. Liu et al [37] used an array that covered 40,173 human lncRNAs to study infection of human neonatal fibroblasts by the type II avirulent strain ME49 strain-4525 lncRNAs were up-regulated, and 1519 lncRNAs were down-regulated, and coding-non-coding co-expression network analyses showed lncRNAs were involved in the expression of multiple immune-related proteins. Menard et al [38] examined differential expression of lncRNAs in mouse bone marrow-derived macrophages infected with the type I virulent RH strain or the type II avirulent PTG strain-893 lncRNAs were up-regulated, and 875 lncRNAs were down-regulated, and gene ontology analyses demonstrated that these lncRNAs participated in many immune-related biological processes [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While our work was in progress, another group used a similar microarray approach to identify lncRNA expression in human foreskin fibroblast cells infected with only Type II T . gondii 60 . In that study, a lncRNA designated NONSHAT022487 was up-regulated during infection of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs were identified as an important regulatory factor that is crucial in regulating immunological stress during cystic echinococcosis, in an experimental mouse model of cystic echinococcosis [19]. In addition, lncRNAs have also been identified as important in the biological functions of other parasites (e.g., Trichomonas vaginalis [36] and Toxoplasma [37]) and in host immunity. Thus, we speculate that lncRNAs may be expressed in Echinococcus spp.…”
Section: Introductionmentioning
confidence: 99%